A review of the role of anti-corruption agencies in implementing sustainable development goals (sdg) - Lokman, Asmidar; Mohd Yusof, Mohd Idham; Rahman, Shamsinar; Mohd Noor, Nurul Hidayana; Sani, Mohtar (GADING Journal for the Social Sciences, 2024)
The United Nations (UN) Agenda for Sustainable Development, released in 2015, is the blueprint for global peace, security, and prosperity. The operation is carried out via the Sustainable Development Goals (SDG), and mobilised by government institutions at the country level based on their strong institution principle. However, public institutions, including the Anti-corruption Agency (ACA), have been riddled with corruption problems affecting the SDG-related sectors. Even though limited, previous studies have discussed the roles of supervising and auditing agencies, such as the ACA, in the SDG context. This study reviewed 19 SCOPUS journal articles from 2015 to 2023, exploring the ACA‟s role in progressing the United Nations‟ SDG16 of establishing effective, accountable and inclusive institutions in Singapore, Hong Kong, Indonesia, South Korea, Thailand, and Malaysia. The review highlights that the ACA‟s roles are organised within the ACA structures to battle corruption and its connection with the SDG. The themes emanating from this review which declares the ACA structures supporting SDG16 are: a) Institutional Reform, b) Good Governance, and c) Anti-Corruption Advocacy. The aim of this paper is to enlighten the current state of ACA intervention for the SDGs and why it should be a part of the SDG Governance Structure. This paper intends to fill the existing gap in literature, particularly in the aspect of institutional capacities, towards contributing to the global agenda of 2030.